2018
DOI: 10.1177/0143034318809762
|View full text |Cite
|
Sign up to set email alerts
|

Authoritative classroom climate and its relations to bullying victimization and bystander behaviors

Abstract: Authoritative school climates have been associated with less school bullying and other antisocial behaviors. However, studies focusing on the classroom level, as well as on bystander behaviors, are lacking. The aim of the current study was to examine whether authoritative classroom climates were associated with bullying victimization and various bystander behaviors (reinforcer, outsider, and defender behaviors) in school bullying. We included gender as a covariate at the individual and classroom levels. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 58 publications
4
41
0
1
Order By: Relevance
“…However, it is important to separate school-level from classroom-level aspects of social climate at school. Whereas the former focuses on aspects such as the feeling of safety at school, the latter highlights the role of the protective quality of social interactions within the classroom (Thornberg et al 2018).…”
Section: School Climate Cyberbullying and Cyberbystander Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to separate school-level from classroom-level aspects of social climate at school. Whereas the former focuses on aspects such as the feeling of safety at school, the latter highlights the role of the protective quality of social interactions within the classroom (Thornberg et al 2018).…”
Section: School Climate Cyberbullying and Cyberbystander Behaviormentioning
confidence: 99%
“…To date, research on the link between school climate and bystander behavior in bullying and cyberbullying episodes is limited. For example, Thornberg et al (2018) investigated the role of an authoritative classroom climate (characterized for example as warm, demanding, cohesive, and supportive) on offline victimization and bystander behavior. Results of their study with early adolescents (mean age 11.5 years) showed that authoritative classrooms are related to more positive reactions of bystanders witnessing a bullying episode.…”
Section: School Climate Cyberbullying and Cyberbystander Behaviormentioning
confidence: 99%
“…그런데 최근 연구자들은 이러한 친사회적 행동의 동기 가 이타적 동기(altruistic motivation)와 이기적 동기(egoistic motivation)로 구분될 수 있다는 Batson 등(1987) (Caravita, Blasio, & Salmivalli, 2009;Oh, 2010). 즉, 선행연구자들은 Batson (1990)의 공감-이타성 모델(Empathy-altruism model) 에 근거하여 괴롭힘 상황에서 방어행동을 보이는 이들이 피해자 에 대한 정서적 공감으로 인해 그러한 도움행동을 수행하게 된 다는 가정을 검증해왔다 (Caravita et al, 2009;Oh, 2010 (Batson et al, 1987 (Dovidio et al, 1991 (Gong & Lee, 2017;Kim, 1994;Thornberg et al, 2018 Gender: male as 0, female as 1. * p<.05, ** p<.01, *** p<.001.…”
Section: 또래괴롭힘 방어행동의 예측 요인과 관련하여 다수의 연구unclassified
“…A positive classroom climate that is supportive of and conducive to student learning, is associated with higher level of student participation [25,26]. Conversely, a chilly climate is associated with low student participation and is thought to adversely affect student learning [27,28]. Among other influences, the instructor's leadership is documented extensively as playing a dominant role in building and guiding the classroom atmosphere [29,30] (also see the paragraph below).…”
Section: Group Dynamics In Shaping Classroom Climatementioning
confidence: 99%